Aspecto da literatura brasileira: o ritmo estético - Fantinati, Carlos Erivany [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Tem-se como objetivo mostrar um dos aspectos da concepção de literatura brasileira desenvolvida por Antonio Candido em um conjunto de textos publicados entre 1953/5 e 1997. Dentre os três aspectos possíveis – os outros dois são o ritmo histórico e social e o sistema literário – o escolhido foi o ritmo estético, regido pela dialética do local e do cosmopolita, que, para o autor, funcionaria como “lei de evolução da nossa vida espiritual”– “se fosse possível estabelecer uma” (CANDIDO, 1965, p.131) –, presente, de modo decisivo, nas formas de expressão de nossa literatura, em cujo processo histórico se manifesta de modo diverso nas várias etapas do longo percurso que vai da dependência do período colonial até a integração na interdependência cultural de nosso tempo. O autor constrói sua concepção de literatura brasileira em tensão com a noção nacionalista de literatura do Brasil, que, de origem romântica, prossegue no Naturalismo e Modernismo, atingindo tempos ulteriores. Complementam a exposição algumas considerações sobre o processo de difusão e recepção das obras que propagam suas idéias, expressões de sua visão de mundo, “fiel à tradição do humanismo ocidental”(CANDIDO, 2008, p.11).

The aim of this paper is to show one of the aspects of the concept of Brazilian literature, as developed by Antonio Candido in a set of texts published between 1953/5 and 1997. There are three possible aspects of analysis, but two of them will not be considered in this study, that is to say, the historical and social rhythm as well as the literary system. The third one is the aesthetic rhythm, which, oriented by the dialectic between the local and the cosmopolitan, would function as a “law of evolution of our spiritual life” [...] “if it were possible to establish one” (CANDIDO, 1965, p. 131). That rhythm is present in a decisive way in the forms of expression of Brazilian literature, as shown in its historical process, in a different fashion, in many phases of the long transition between the dependence of the Colonial Period and the integration to the cultural interdependence of our time. The author’s concept of Brazilian Literature is developed in tension with the nationalist view of literature from Brazil, of Romantic origin and still present in Naturalism and Modernism, until later times. The exposition of this paper is complemented by some considerations about the process of diffusion and reception of the works which spread Candido's ideas - expressions of his world view, which is faithful to the tradition of Western Humanism (CANDIDO, 2008, p. 11).
Aspect of Brazilian literature: the aesthetic rhythm
Keywords: Brazilian literature; History; Forms of expression; Dialectic between the local and the cosmopolitan; Antonio Candido; Nationalism; Literatura brasileira; História; Formas de expressão; Dialética do local e do cosmopolita; Nacionalismo